Photoinduced fragmentation-rearrangement sequence of cycloketoxime esters. Issue 18 (22nd August 2018) - Zhao, Binlin; Chen, Cheng; Lv, Jiahang; Li, Zexian; Yuan, Yu; Shi, Zhuangzhi
Abstract : A novel rearrangement of cycloketoxime esters to cyano-containing benzoates beyond the traditional Beckmann and Neber rearrangement process has been established in the presence of photocatalysis catalysis. Abstract : A novel rearrangement of cycloketoxime esters to cyano-containing benzoates beyond the traditional Beckmann and Neber rearrangement process has been established in the presence of photocatalysis catalysis. This SET-induced structural reorganization of cycloketoxime esters is perfectly an atom economic process and distinguished by mild and safe reaction conditions that avoid acid, base and toxic cyanide salts.